Shooting Victoria madness, mayhem, and the rebirth of the British monarchy - Murphy, Paul Thomas 1957- (Pegasus Books, 2012)
From a hunchbacked dwarf to a paranoid poet assassin, a history of Victorian England as seen through the numerous assassination attempts on Queen Victoria